STABILITAS NONPARAMETRIK HASIL 14 GENOTIPE TOMAT (Solanum lycopersicum L.) DI EMPAT LINGKUNGAN - Dewi, Suprayanti Martia; Sobir, Sobir; Syukur, Muhamad; Kisman, Kisman (AGROTEKSOS, 2023)
This study aimed to obtain information yield stability of 14 tomato genotypes grown in four lowland locations using some nonparametric methods of stability analysis. The experiments were conducted at four locations, there was Purwakarta, Lombok, Tajur and Leuwikopo. Experiments at each location using Randomized Complete Block Design (RCBD) with three replications which replicates nested within location. Based on nonparametric stability index values, the stable genotypes in the lowlands by the Thennarassu and Nassar & Huehn methods were IPBT33, IPBT34 and IPBT60 with the productivity respectively 15.69, 18,37 and 20,26 tonnes ha –1 .